A biomass-based carbon phosphide material and its application

Through the preparation of biomass-based carbon phosphide materials, combined with carbon black and PVDF, the problem of insufficient performance of sodium ion battery negative electrode materials is solved, and high specific capacity and good rate performance is achieved, which is suitable for industrial applications.

CN117509611BActive Publication Date: 2025-01-03BEIJING UNIV OF CHEM TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311670719.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-07
Publication Date
2025-01-03
Estimated Expiration
2043-12-07

AI Technical Summary

Technical Problem

In actual applications, existing sodium ion battery negative electrode materials have problems such as low first-term efficiency, poor capacity and rate performance, and the sodium ion embedding/deintercalation efficiency is low, making it difficult to achieve commercial application.

Method used

Using biomass-based carbon phosphide material, through the reaction of biomass polysaccharides with Schiff base and phosphide addition of vanillin, a carbon material with uniform structure and low graphitization degree is formed, combined with carbon black and PVDF for grinding, and prepared Suitable for sodium ion battery negative electrode materials, and the material performance is regulated through specific high-temperature sintering processes.

Benefits of technology

It has achieved high specific capacity and good rate performance of the negative electrode material of sodium ion battery, and has good cycle stability and sodium storage ability, which is suitable for industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117509611B_ABST
    Figure CN117509611B_ABST
Patent Text Reader

Abstract

A biomass-based phosphide carbon material and its application, which belongs to the field of metal ion battery negative electrode materials. Functional groups are introduced into polysaccharide molecules by chemical reaction, and the functional groups are further used for chemical reaction to regulate the structure of polysaccharide molecules, that is, biomass polysaccharide and vanillin undergo Schiff base reaction to graft vanillin onto the polysaccharide molecular side chain to form a polysaccharide intermediate. Subsequently, an addition reaction occurs with the phosphide to further expand the side chain to form a biomass-based carbon material precursor. During the high-temperature sintering process, the precursor molecules can further undergo chemical reaction to form larger molecular clusters, which have a low degree of graphitization after sintering, more surface defects, and good sodium storage capacity. Used as the negative electrode of a sodium ion battery, it exhibits a high sodium storage capacity and a good capacity retention rate. This material is a new type of sodium storage carbon material, with abundant and easy-to-obtain raw materials, a simple production process, mild reaction conditions, and safety and environmental protection.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of metal ion battery negative electrode materials, and specifically relates to a biomass-based carbon phosphide material and an application thereof. Background Art

[0002] As humans develop and utilize energy, energy crises are caused, and a large amount of harmful substances such as CO2, NO and SO2 are produced, which seriously affect the environment. Although energy storage devices such as wind power and solar energy have been used to relieve the pressure on the power grid, the current priority is to develop low-cost secondary batteries without resource restrictions to solve the problem of resource shortage.

[0003] Lithium-ion batteries are typical secondary batteries and are widely used due to their high energy density. However, due to the lack of lithium resources, the cost is too high, so the development of low-cost secondary batteries is urgent. Sodium has similar chemical properties to lithium, and sodium-ion batteries have lower energy density, but sodium resources are abundant and the cost is low. Commercial lithium-ion batteries use graphite as the anode and have high energy density, but the ionic radius of sodium ions is larger than that of lithium ions and cannot be smoothly embedded in graphite. Therefore, it is necessary to develop a negative electrode material that is conducive to the embedding / de-embedding of sodium ions and has high energy density, good rate performance and cycle stability to realize the commercial application of sodium-ion batteries.

[0004] Hard carbon materials are difficult to graphitize, have uneven pore distribution and many defects, and have large carbon layer spacing, which can provide more active sites for sodium ions and accelerate the embedding / deintercalation of sodium ions in hard carbon, resulting in hard carbon materials having higher specific capacity. Therefore, hard carbon is widely used as negative electrode material for sodium ion batteries. However, hard carbon negative electrode materials also face problems such as low initial efficiency, low capacity and rate performance in practical applications. Summary of the invention

[0005] In order to overcome the deficiencies in the prior art, the present invention aims to provide a biomass-based carbon material with uniform structure, stable performance, simple production process, and low graphitization degree and its sodium ion battery application method. Using biomass polysaccharide as the main material, by doping heteroatoms to improve its performance, a biomass-based carbon negative electrode material with adjustable structure, simple method and high carbon yield is prepared, which is very suitable as a negative electrode material for sodium ion batteries.

[0006] In order to achieve the above-mentioned purpose of the invention and solve the problems existing in the prior art, the technical solution of the present invention is: a method for preparing a biomass-based carbon phosphide material, comprising the following steps:

[0007] (1) Dispersing biomass polysaccharide and vanillin in ethanol, sealing, heating and stirring for 6-10 hours, filtering, washing and drying after the reaction is completed to obtain intermediate A;

[0008] The molar ratio of the biomass polysaccharide to vanillin is 1:(0.5-5);

[0009] (2) Dispersing the intermediate A and the phosphide in ethanol, heating and stirring for 6-10 hours, filtering, washing and drying after the reaction is completed, to obtain a polysaccharide precursor;

[0010] The molar ratio of the intermediate A to the phosphide is 1:(0.5-5);

[0011] (3) The polysaccharide precursor is placed in a porcelain boat, placed in a tubular furnace for carbonization treatment, and argon is pre-passed. Under the protection of the argon atmosphere, the temperature is raised to 300°C-500°C and the reaction is carried out for 0.5h-8h; under the protection of the argon atmosphere, the temperature is further raised to 1000°C-1400°C and kept warm for 1-3h. After cooling, the carbon phosphide material is obtained.

[0012] The biomass polysaccharide is one or more of chitin, chitosan, chitosan oligosaccharide, chitosan and mucopolysaccharide.

[0013] The phosphide is 2-carboxyethyl phosphoric acid, trihydroxymethyl phosphorus oxide, phenyl phosphorus dichloride, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, sodium dihydrogen phosphate, disodium hydrogen phosphate, diammonium hydrogen phosphate or sodium hypophosphite.

[0014] Furthermore, the heating temperature in step (1) is 40-120°C.

[0015] Furthermore, the heating temperature in step (2) is 40-120°C.

[0016] Furthermore, in step (3), the heating rate is 3, 5, 8, or 10°C / min.

[0017] The carbon phosphide material is used in the negative electrode material of sodium ion batteries.

[0018] Furthermore, the present invention provides a method for phosphating biomass-based carbon materials, which effectively adjusts the molecular structure of polysaccharides uniformly by increasing loadable functional groups, and has good repeatability. It is added to coal as a hard carbon precursor to adjust the sodium storage performance of coal-based functional carbon materials; the method comprises the following steps:

[0019] (1) adding polysaccharide and vanillin into a solvent at a molar ratio of 1:(0..5-5) to dissolve and mix;

[0020] (2) heating the mixed solution to 60°C-90°C, stirring and reacting at a constant temperature for 0.5h-10.5h, and filtering to obtain a polysaccharide intermediate;

[0021] (3) adding the polysaccharide intermediate and the phosphide into a solvent at a molar ratio of 1:(0-5) to dissolve and mix;

[0022] (4) raising the temperature to 60° C.-90° C. under sealed conditions, stirring and reacting at a constant temperature for 0.5 h-10.5 h, filtering and drying for 24 h to obtain a hard carbon precursor;

[0023] (5) The biomass-based carbon material precursor powder prepared above is loaded into a porcelain boat and placed in a tube furnace, and the temperature is raised to 400° C.-500° C. under an inert gas atmosphere, and kept at this temperature for 0.5-10 hours to allow a cross-linking reaction to occur;

[0024] (6) After the cross-linking reaction is completed, the temperature is further raised to 1000°C-1500°C in an inert gas atmosphere and kept at this temperature for 0.5-10 hours to cause a cracking reaction. After cooling, a coal-based functional carbon material is obtained. Preferably, the heating rate in steps (5)-(6) is 0.5-10°C / min, and preferably the heating rate is 3, 5, 8, or 10°C / min.

[0025] Preferably, the polysaccharide comprises one or more of chitin, chitosan, chitosan oligosaccharide, chitosan and mucopolysaccharide.

[0026] Preferably, the phosphide includes phosphorus-containing organic substances such as 2-carboxyethylphosphoric acid, trishydroxymethylphosphine oxide, phenylphosphine dichloride, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, and phosphorus-containing inorganic substances such as sodium dihydrogen phosphate, disodium hydrogen phosphate, diammonium hydrogen phosphate, and sodium hypophosphite. Preferably, the constant temperature stirring includes any one or more of a water bath, a sand bath, an oil bath, and a reactor. The dissolving and mixing includes one or more of stirring, heating, and ultrasonic dispersion.

[0027] Preferably, the mechanical mixing includes any one or more of mechanical stirring, ball milling, grinding, and ultrasonic dispersion.

[0028] The biomass-based carbon material is ground and mixed with carbon black and PVDF in a mass ratio of 8:1:1. After mixing evenly, an appropriate amount of NMP is added to grind into a slurry with a certain viscosity, and evenly coated on a copper foil with a scraper, vacuum dried at 80°C for 12 hours, cut into round pole pieces of appropriate size, weighed and transferred to a glove box for standby use. The half-cell is assembled in an argon-filled glove box, with metallic sodium as the counter electrode and 1 mol / L sodium trifluoromethanesulfonate dissolved in diethylene glycol dimethyl ether as the electrolyte. The positive electrode shell, positive pole piece (sodium sheet), glass fiber diaphragm, electrolyte, negative pole piece, and negative electrode shell are stacked in sequence and sealed with a sealing machine to complete the sodium ion battery assembly. Sodium ion batteries are used in mobile devices, new energy vehicles, battery components, hydropower generation, wind power generation, smart grid peak regulation, distributed power stations, backup power supplies or large-scale energy storage devices for communication base stations.

[0029] The beneficial effects of the present invention are:

[0030] In the present invention, a functional group is introduced into the polysaccharide molecule by chemical reaction, and the functional group is further used for chemical reaction to regulate the structure of the polysaccharide molecule, that is, the biomass polysaccharide reacts with vanillin to graft the vanillin onto the branch chain of the polysaccharide molecule to form a polysaccharide intermediate. Then, an addition reaction occurs with the phosphide to further expand the branch chain to form a biomass-based carbon material precursor.

[0031] During the high-temperature sintering process, the precursor molecules can further undergo chemical reactions to form larger molecular clusters. After sintering, the degree of graphitization is low, and there are more surface defects, which have good sodium storage capacity. Compared with other processes, this process has mild reaction conditions, abundant raw materials, and is used for carbon-based negative electrodes of sodium ion batteries. It has stable specific capacity and rate performance, which is conducive to industrial application. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 This is a charge and discharge curve diagram of the biomass-based carbon phosphide material prepared in Example 1 as the negative electrode of a sodium ion battery.

[0033] Figure 2 This is a charge and discharge curve diagram of the biomass-based carbon phosphide material prepared in Example 2 as the negative electrode of a sodium ion battery.

[0034] Figure 3 This is a charge and discharge curve diagram of the biomass-based carbon phosphide material prepared in Example 3 as the negative electrode of a sodium ion battery.

[0035] Figure 4 This is a charge and discharge curve diagram of the biomass-based carbon phosphide material prepared in Example 4 as the negative electrode of a sodium ion battery. DETAILED DESCRIPTION

[0036] The present invention will be further described below in conjunction with the embodiments.

[0037] Example 1

[0038] Example 1 of the present invention provides a method for synthesizing a biomass-based carbon precursor. The material is synthesized by chemical reaction of chitosan oligosaccharide, vanillin and sodium hypophosphite.

[0039] Dissolve 6.09g of vanillin in 40ml of anhydrous ethanol, add 5g of chitosan oligosaccharide, stir and heat in an 80℃ oil bath for 8h, and filter to obtain intermediate A. Dissolve 4.24g of sodium hypophosphite in 40ml of anhydrous ethanol, add intermediate A, seal, stir and heat in an 80℃ oil bath for 8h. Filter, wash, and dry for 24h to obtain the biomass-based carbon precursor.

[0040] The biomass-based carbon precursor is loaded into a porcelain boat and placed in a tubular furnace. Argon gas is pre-flowed for 0.5 h at room temperature to remove the air in the tube; the temperature is increased to 400°C at a rate of 5°C / min in an argon atmosphere and kept warm for 2 hours; the temperature is continued to be increased to 1200°C at a rate of 5°C / min in an argon atmosphere and kept warm for 2 hours to allow the precursor to fully undergo a cracking reaction; after it is cooled to room temperature, the sample is taken out to obtain a biomass-based carbon phosphide material, which is used as a negative electrode material for sodium ion batteries.

[0041] The biomass-based carbon phosphide material prepared by the above steps is used as the negative electrode material of the sodium ion battery to assemble the sodium ion battery.

[0042] The biomass-based carbon material was ground and mixed with carbon black and PVDF in a mass ratio of 8:1:1. After mixing evenly, an appropriate amount of NMP was added and ground into a slurry with a certain viscosity. The slurry was evenly coated on a copper foil with a scraper, vacuum dried at 80°C for 12 hours, cut into round pole pieces of appropriate size, weighed and transferred to a glove box for standby use. The half-cell was assembled in an argon-filled glove box, with metallic sodium as the counter electrode and 1 mol / L sodium trifluoromethanesulfonate dissolved in diethylene glycol dimethyl ether as the electrolyte. The positive electrode shell, positive pole piece (sodium sheet), glass fiber diaphragm, electrolyte, negative pole piece, and negative electrode shell were stacked in sequence and sealed with a sealing machine to complete the sodium ion battery assembly.

[0043] The assembled sodium ion battery was subjected to electrochemical charge and discharge tests with a test voltage range of 0.01V-3V. The test results are shown in Figure 1 , the reversible specific capacity is 203.7 mAh g -1 The first coulombic efficiency is 81.19%, with good cycle stability.

[0044] Example 2

[0045] Example 1 of the present invention provides a method for synthesizing a biomass-based carbon precursor. The material is synthesized by chemical reaction of chitosan, vanillin and sodium hypophosphite.

[0046] Dissolve 6.09g of vanillin in 40ml of anhydrous ethanol, add 5g of chitosan, stir and heat in an 80℃ oil bath for 8h, and filter to obtain intermediate A. Dissolve 4.24g of sodium hypophosphite in 40ml of anhydrous ethanol, add intermediate A, seal, stir and heat in an 80℃ oil bath for 8h. Filter, wash, and dry for 24h to obtain the biomass-based carbon precursor.

[0047] The biomass-based carbon precursor is loaded into a porcelain boat and placed in a tubular furnace. Argon gas is pre-flowed for 0.5 h at room temperature to remove the air in the tube; the temperature is increased to 400°C at a rate of 5°C / min in an argon atmosphere and kept warm for 2 hours; the temperature is continued to be increased to 1200°C at a rate of 5°C / min in an argon atmosphere and kept warm for 2 hours to allow the precursor to fully undergo a cracking reaction; after it is cooled to room temperature, the sample is taken out to obtain a biomass-based carbon phosphide material, which is used as a negative electrode material for sodium ion batteries.

[0048] The biomass-based carbon phosphide material prepared by the above steps is used as the negative electrode material of the sodium ion battery to assemble the sodium ion battery.

[0049] The biomass-based carbon material was ground and mixed with carbon black and PVDF in a mass ratio of 8:1:1. After mixing evenly, an appropriate amount of NMP was added and ground into a slurry with a certain viscosity. The slurry was evenly coated on a copper foil with a scraper, vacuum dried at 80°C for 12 hours, cut into round pole pieces of appropriate size, weighed and transferred to a glove box for standby use. The half-cell was assembled in an argon-filled glove box, with metallic sodium as the counter electrode and 1 mol / L sodium trifluoromethanesulfonate dissolved in diethylene glycol dimethyl ether as the electrolyte. The positive electrode shell, positive pole piece (sodium sheet), glass fiber diaphragm, electrolyte, negative pole piece, and negative electrode shell were stacked in sequence and sealed with a sealing machine to complete the sodium ion battery assembly.

[0050] The assembled sodium ion battery was subjected to electrochemical charge and discharge tests with a test voltage range of 0.01V-3V. The test results are shown in Figure 2 , the reversible specific capacity is 213.8 mAh g -1 The first coulombic efficiency is 76.7%, with good cycle stability.

[0051] Example 3

[0052] Embodiment 1 of the present invention provides a method for synthesizing a biomass-based carbon precursor. The material is synthesized by chemical reaction of chitosan, vanillin and DOPO.

[0053] Dissolve 6.09g of vanillin in 40ml of anhydrous ethanol, add 5g of chitosan, stir and heat in an 80℃ oil bath for 8h, and filter to obtain intermediate A. Dissolve 8.83g of DOPO in 40ml of anhydrous ethanol, add intermediate A, seal, stir and heat in an 80℃ oil bath for 8h. Filter, wash, and dry for 24h to obtain the biomass-based carbon precursor.

[0054] The biomass-based carbon precursor is loaded into a porcelain boat and placed in a tubular furnace. Argon gas is pre-flowed for 0.5 h at room temperature to remove the air in the tube; the temperature is increased to 400°C at a rate of 5°C / min in an argon atmosphere and kept warm for 2 hours; the temperature is continued to be increased to 1200°C at a rate of 5°C / min in an argon atmosphere and kept warm for 2 hours to allow the precursor to fully undergo a cracking reaction; after it is cooled to room temperature, the sample is taken out to obtain a biomass-based carbon phosphide material, which is used as a negative electrode material for sodium ion batteries.

[0055] The biomass-based carbon phosphide material prepared by the above steps is used as the negative electrode material of the sodium ion battery to assemble the sodium ion battery.

[0056] The biomass-based carbon material was ground and mixed with carbon black and PVDF in a mass ratio of 8:1:1. After mixing evenly, an appropriate amount of NMP was added and ground into a slurry with a certain viscosity. The slurry was evenly coated on a copper foil with a scraper, vacuum dried at 80°C for 12 hours, cut into round pole pieces of appropriate size, weighed and transferred to a glove box for standby use. The half-cell was assembled in an argon-filled glove box, with metallic sodium as the counter electrode and 1 mol / L sodium trifluoromethanesulfonate dissolved in diethylene glycol dimethyl ether as the electrolyte. The positive electrode shell, positive pole piece (sodium sheet), glass fiber diaphragm, electrolyte, negative pole piece, and negative electrode shell were stacked in sequence and sealed with a sealing machine to complete the sodium ion battery assembly.

[0057] The assembled sodium ion battery was subjected to electrochemical charge and discharge tests with a test voltage range of 0.01V-3V. The test results are shown in Figure 3 , the reversible specific capacity is 295.47 mAh g -1 The first coulombic efficiency is 88.85%, with good cycle stability.

[0058] Example 4

[0059] Example 1 of the present invention provides a method for synthesizing a biomass-based carbon precursor. The material is synthesized by chemical reaction of chitosan, vanillin and DOPO.

[0060] Dissolve 6.09g of vanillin in 40ml of anhydrous ethanol, add 5g of chitosan, stir and heat in an 80℃ oil bath for 8h, and filter to obtain intermediate A. Dissolve 8.83g of DOPO in 40ml of anhydrous ethanol, add intermediate A, seal, stir and heat in an 80℃ oil bath for 8h. Filter, wash, and dry for 24h to obtain the biomass-based carbon precursor.

[0061] The biomass-based carbon precursor is loaded into a porcelain boat and placed in a tubular furnace. Argon gas is pre-flowed for 0.5 h at room temperature to remove the air in the tube; the temperature is increased to 400°C at a rate of 5°C / min in an argon atmosphere and kept warm for 2 hours; the temperature is continued to be increased to 1200°C at a rate of 5°C / min in an argon atmosphere and kept warm for 2 hours to allow the precursor to fully undergo a cracking reaction; after it is cooled to room temperature, the sample is taken out to obtain a biomass-based carbon phosphide material, which is used as a negative electrode material for sodium ion batteries.

[0062] The biomass-based carbon phosphide material prepared by the above steps is used as the negative electrode material of the sodium ion battery to assemble the sodium ion battery.

[0063] The biomass-based carbon material was ground and mixed with carbon black and PVDF in a mass ratio of 8:1:1. After mixing evenly, an appropriate amount of NMP was added and ground into a slurry with a certain viscosity. The slurry was evenly coated on a copper foil with a scraper, vacuum dried at 80°C for 12 hours, cut into round pole pieces of appropriate size, weighed and transferred to a glove box for standby use. The half-cell was assembled in an argon-filled glove box, with metallic sodium as the counter electrode and 1 mol / L sodium trifluoromethanesulfonate dissolved in diethylene glycol dimethyl ether as the electrolyte. The positive electrode shell, positive pole piece (sodium sheet), glass fiber diaphragm, electrolyte, negative pole piece, and negative electrode shell were stacked in sequence and sealed with a sealing machine to complete the sodium ion battery assembly.

[0064] The assembled sodium ion battery was subjected to electrochemical charge and discharge tests with a test voltage range of 0.01V-3V. The test results are shown in Figure 4 , the reversible specific capacity is 278.7 mAh g -1 The first coulombic efficiency is 89.45%, with good cycle stability.

Claims

1. A method for preparing a biomass-based carbon phosphide material, characterized in that: The steps include: (1) Dispersing biomass polysaccharides and vanillin in ethanol, sealing, heating and stirring for 6-10 hours, filtering, washing and drying after the reaction is completed to obtain intermediate A; The molar ratio of the biomass polysaccharide to vanillin is 1:(0.5-5); (2) Dispersing intermediate A and phosphide in ethanol, heating and stirring for 6-10 hours, filtering, washing and drying after the reaction is completed, to obtain a polysaccharide precursor; The molar ratio of the intermediate A to the phosphide is 1:(0.5-5); (3) The polysaccharide precursor is placed in a porcelain boat and placed in a tube furnace for carbonization treatment. Argon is pre-flowed. Under the protection of argon atmosphere, the temperature is raised to 300°C-500°C and the reaction is carried out for 0.5 h-8 h. Under the protection of argon atmosphere, the temperature is further raised to 1000°C-1400°C and kept at this temperature for 1-3 h. After cooling, the carbon phosphide material is obtained. The biomass polysaccharide is one or more of chitin, chitosan, chitosan oligosaccharide, chitosan and mucopolysaccharide; The phosphide is 2-carboxyethyl phosphoric acid, trihydroxymethyl phosphorus oxide, phenyl phosphorus dichloride, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, sodium dihydrogen phosphate, disodium hydrogen phosphate, diammonium hydrogen phosphate or sodium hypophosphite; The heating temperature in step (1) is 40-120°C; The heating temperature in step (2) is 40-120°C.

2. The method for preparing a biomass-based carbon phosphide material according to claim 1, characterized in that: The heating rates in step (3) are 3, 5, 8, and 10 °C / min.

3. The use of the carbon phosphide material prepared by the method according to any one of claims 1-2, characterized in that: The carbon phosphide material is used in the negative electrode material of sodium ion batteries.